Penerapan Protokol Kesehatan 5 M (Mencuci Tangan, Memakai Masker, Menjaga Jarak, Menjauhi Kerumunan, Mengurangi Mobilitas) di TPQ Al-Masy Dingin Ngronggot - Abdul Basit Misbachul Fitri; Muhammad Shinwanuddin; Afiful Huda (Janaka, Jurnal Pengabdian Masyarakat, 2022)
The current COVID-19 pandemic in Indonesia has not shown a significant decline, because there are still many big cities implementing health protocols, but in several other areas experiencing a rapid decline. Educational institutions are the spearhead of the government in educating the nation, in any situation educational institutions must exist in carrying out their duties by obtaining security and health guarantees. For this reason, the existence of KPM is carried out at the Al-Qur'an Education Park as the program for implementing the 5M prokes (washing hands, wearing masks, keeping distance, staying away from crowds, reducing mobility) at the Al-Qur'an Education Park al-Masy Cold Ngronggot with aims to provide education (education) to the public on the importance of implementing health protocols in accordance with Presidential Instruction No. 06 of 2020 in order to maintain joint health in carrying out institutional activities. The KPM team together with stake holders, namely the al-Masy educational foundation, asatidz, TPQ female students get convenience in realizing the program, so this program recommends to female students, asatidz and guardians of students to continue to apply health protocols.